Una aproximación al constitucionalismo latinoamericano, características principales y nuevas tendencias - Hakansson, Carlos (Revista de Derecho Político, 2017)
Resumen: El presente trabajo es una primera aproximación a las diversas manifestaciones del constitucionalismo en América Latina, a partir de algunas referencias comunes: Revolución Francesa, Derecho Comparado y alusiones a la modernidad. Summary: I. The common traits of the latin american constitutions. II. Content of the latin american constitutions. III. The degree of modernity of the latin american constitutions. IV. Constitutional trends. V. An approach to ibero-american presidential model. VI. Prospects for latin american constitutionalism. Abstract: The present paper is a first approximation on the diverse manifestations of the constitutionalism in Latin America, starting from some common references: French Revolution, Comparative Law, and allusions to modernity.